Identification of key genes controlling L-ascorbic acid during Jujube (Ziziphus jujuba Mill.) fruit development by integrating transcriptome and metabolome analysis - Lu, Dongye; Wu, Yang; Pan, Qinghua; Zhang, Yuping; Qi, Yuanyong; Bao, Wenhui (Frontiers in Plant Science, 2022)
Chinese jujube (Ziziphus jujuba) is a vital economic tree native to China. Jujube fruit with abundant L-Ascorbic Acid (AsA) is an ideal material for studying the mechanism of AsA biosynthesis and metabolism. However, the key transcription factors regulating AsA anabolism in jujube have not been reported. Here, we used jujube variety ‘Mazao’ as the experimental material, conducted an integrative analysis of transcriptome and metabolome to investigate changes in differential genes and metabolites, and find the key genes regulating AsA during jujube fruit growth. The results showed that AsA was mostly synthesized in the young stage and enlargement stage, ZjMDHAR gene takes an important part in the AsA recycling. Three gene networks/modules were highly correlated with AsA, among them, three genes were identified as candidates controlling AsA, including ZjERF17 (LOC107404975), ZjbZIP9 (LOC107406320), and ZjGBF4 (LOC107421670). These results provide new directions and insights for further study on the regulation mechanism of AsA in jujube.